Tara (Caesalpinia spinosa) in Natural and Agroforestry Systems under an Altitudinal Gradient in the Peruvian Andes: Responses to Soil and Climate Variation. - Murga-Orrillo, Hipolito (2023)
Abstract: This research examined how edaphoclimatic variations are related to dendrometric variables of the Tara tree in natural and agroforestry systems in Cajamarca, Peru. Evaluations followed three approaches: (a) principal components analysis (PCA) with environmental factors and altitude classes with 1 ◦C of temperature variation for edaphic and dendrometric variables; (b) evaluation of possible differences by the bootstrap method for the different variables in the PCAs; and (c) correlation analysis between plant density, plant and crown height, stem and crown diameter, and the number of stem branches with the physical and chemical attributes of the soil and with air temperature. In the altitudinal gradient from 2021 to 3007 ± 7 m, the temperature ranged from 19.8 to 13.4 ± 0.4 ◦C; the soils possessed alkaline pH, high organic matter (OM), K and CEC, lower contents of CaCO3, N, P, K, B, Cu, Fe, Mn, and Zn. The soil properties with the most significant contribution to PCAs were OM, CEC, N content, and sand, with no variation among environments but among altitudes. None of the dendrometric variables varied as a function of altitude and temperature in PCAs run in the natural environment. However, in the agroforestry environment, there was a greater crown diameter, and tree and crown height in the 2185 m altitude class associated with Medicago sativa. In contrast, the opposite behavior was found in these variables and in the altitude class 2798 m associated with low Fe content, and already in the altitude class at 3007 m, a larger stem diameter is associated with higher levels of CaCO3 . The anthropic effect on the agroforestry environment did not significantly alter the soil’s CEC, OM, N, and sand. Tara’s crown diameter and tree height appeared higher in agroforestry environments. The variations of Fe and CaCO3 in the soil might have influence on the development of Tara individuals in natural and agroforestry environments. It is important to carry out further studies for a better understanding of the relationship between the production of Tara pods and soil fertility in altitudinal variation, aiming to improve the income and employment of family farmers who exploit Tara in the Peruvian Andes.